The gender pay gap for private sector employees in Canada and Britain - Marie Drolet; Karen Mumford (Institute for the Study of Labor (IZA), 2009)
Country-specific factors, such as the wage setting environment, are important determinants in explaining the relative size of the gender wage gap. This paper uses British and Canadian linked employer-employee data to investigate the importance of the workplace for the gender wage gap. Our main findings are that the unadjusted gender earnings gaps are similar between the two countries and that women, especially older women, are disproportionately represented in low-wage workplaces. Workplace effects, however, reduce the wage gap by 14.5% in Canada and increase the gap by 3.2% in Britain.
urn:nbn:de:101:1-20090209279
Keywords: J16; J0; 330; Gender earnings gap; workplaces; Britain; Canada; Lohndifferenzierung; Arbeitsplatz; Frauenarbeitslohn; Großbritannien; Kanada